Contaminated Patterns of Multi-clause Sentences Containing More than two Clauses in Old English (Based on Anglo-Saxon Chronicle) - Стыро, В. (Kalbotyra, 1972)
Sentences containing contamination of consecutive (stepwise) subordination and coordination o» clauses are described. Contaminated sentence-patterns structure and distribution of dependent clauses are analysed. The quantative distribution of variant patterns is defined.